Perspectivas históricas do ensino de ciências e das atividades experimentais no Brasil - Szymanski, Aline (2019)
This research aimed to investigate the historical process of Science Teaching and the insertion of experimental activities in the contemporary Brazilian school. Among the many questions raised about the problems surrounding this process, the main one concerns the distance between theory and practice. That is, knowledge of the natural sciences, living knowledge, full of curiosities and explanations about the phenomena surrounding human life, usually appears in school only in the form of abstraction, more like a dead knowledge, making it difficult to involve students in the study of school content. Thus, the concepts are presented in a decontextualized and ahistorical way, restricted to an area of knowledge. In order to reflect on these issues, we resorted to the main theorists who supported the teaching-learning processes in Brazil. This analysis made it possible to understand the teaching and learning process, consequently, to reflect on the role of teachers and, in this perspective, on the meaning of experimental activity. Assuming that teaching and learning processes do not take place in a vacuum, it has become important to understand the historical foundations of science teaching in contemporary school, until reaching experimental activity in the school environment. Given the multiple divisions in the production system and in the area itself, it was necessary to reflect on how the discipline of science was constituted in the contemporary school, especially regarding Brazil. In this sense, the following research questions were raised: What are the theoretical and pedagogical assumptions that underlie Science Teaching and the use of experimental activities in the classroom? What is the historical course of modern science? How did science get into school education? How was the insertion of the science discipline in the Brazilian federal legislation? From when, how and for what reasons were experimental activities defended and implemented in school education and science education? It is concluded that science teaching supported by experimental activities has only recently been included in Brazilian federal legislation. However, science teaching by technique alone does not allow meaningful learning that promotes a conscious and integrated reading of the world. Understanding that the teacher has a fundamental role in the teaching and learning processes, it is considered important to implement public policies aimed at teacher education, allied to the constitution of spaces that allow experimental activities permeated by the reflection on Science and the multiple relationships involved in socio-historical development.